PENGARUH MODEL PEMBELAJARAN GENERATIF DISERTAI CONCEPT MAPPING TERHADAP HASIL BELAJAR DAN KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN FISIKA DI SMAN TEMPEH - Novida Ismiazizah; Trapsilo Prihandono; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2017)
This research aimed to study the effect of Generatif learning model onstudents result of study and students science process skills . This type of researchwas experimental research by one group pretest-posttest design. This research wasconducted in SMAN Tempeh. Population in this study were students of class XI atSMAN Tempeh 2016/2017. Samples were taken with cluster random sampling, XIIPA 4 as an sample class. The techniques of data collection were observation,interviews, documentation, portfolios, and testing. The technique of data analysisused independent sample t-test. The results of this analysis were obtainedsignificance value of 0,000 for students result of study and students science processskills is on very good criteria. It can be concluded that model of Generatif learninggive significantly effect on students result of study and students science processskills is on very good criteria in physics learning at SMAN Tempeh.Key words: Generatif learning model, students result of study, students science processskills